Factor V inhibitor in neonatal intracranial hemorrhage secondary to severe congenital factor V deficiency - Lee, Way Seah; Chong, L.A.; Begum, S.; Abdullah, W.A.; Koh, M.T.; Lim, E.J. (Lippincott, Williams & Wilkins, 2001)
We report a newborn infant girl, born to consanguine ous parents, with recurrent intracranial hemorrhage secondary to congenital factor V deficiency with factor V inhibitor. Repeated transfusions of fresh-frozen plasma (FFP) and platelet concentrates, administrations of immunosuppressive therapy (prednisolone and cyclophosphamide), and intravenous immunoglobulin failed to normalize the coagulation profiles. Exchange transfusion followed-up by administrations of activated prothrombin complex and transfusions of FFP and platelet concentrates caused a temporary normalization of coagulation profile, enabling an insertion of ventriculoperitoneal (VP) shunt for progressive hydrocephalus. The treatment was complicated by thrombosis of left brachial artery and ischemia of left middle finger. The child finally died from another episode of intracranial hemorrhage 10 days after insertion of the VP shunt.